Development of E-ATCM (Accounting Trading Company Module) as an Interactive Digital Learning Media During the Covid-19 Pandemic - Nirbita, Betanika Nila; Sartika, Sri Hardianti (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2021)
This study aims to analyze the feasibility of implementing E-ATCM (Accounting Trading Company Module) in the Basic Financial Accounting Course for Economic Education during the Covid-19 Pandemic. The research method uses Research and Development, which is limited to research procedures to product feasibility tests. The instrument used in the E-ATCM feasibility test is in the form of a questionnaire, which consists of media validation tests by experts, and field tests by students. The data analysis technique was carried out with qualitative descriptive data analysis to determine improvement decisions in the development of E-ATCM. From this research, it shows that the E-ATCM media is suitable for use as a learning media for Basic Financial Accounting during the Covid-19 Pandemic. The value of the feasibility of learning media based on material experts is 94.64%, media experts 93%, linguists 90.65%, and practical experts 94.85%. The percentage of material, media, language, and practical experts is in very decent criteria. The next stage is a limited trial with a value of 85.94% on a very feasible criterion and a broad trial with a value of 90.98% on a very feasible criterion. So it can be concluded that the E-ATCM media is suitable for learning in Basic Financial Accounting courses.